DiarrheagenicEscherichia coliisolates from neonatal alpacas mainly display F17 fimbriae adhesion gene - Siuce, Juan (2020)
Neonatal domestic South American Camelid llamas and alpacas suffer from an enteric disease complex characterized by abdominal distention, lethargy, dehydration, and eventual fatal septicemia. Analysis of rectal swabs from neonatal alpacas suffering clinical diarrheas has constantly isolatedEscherichia coli, mainly the EPEC and EHEC pathotypes. The present communication reports the results of molecular analysis of 226E. colistrains from neonatal alpaca rectal swabs. The isolates were initially tested by multiple PCR, to identifyE. colivirulence geneseae,bfp,Lt,Stx1,Stx2,sta,stab, andltgenes and a similar test to detect F4, F5, F6, F17, and F41fimbriae adhesin genes. Forty-two of the 226 (18.5%) isolates tested positive for at least one pathogenic gene, 25 of the 42 were classified as EPEC (3 positives for onlyeaeand 22 for botheaeandbfp) and the remaining 17 were classified as EHEC. Twenty-four (57%) of the 42 isolates tested positive to F17 adhesin while one was positive for both F6 and F17.